2018
DOI: 10.48550/arxiv.1807.11100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergence of Curve Shortening Flow to Translating Soliton

Abstract: This paper concerns with the asymptotic behavior of complete non-compact convex curves embedded in R 2 under the α-curve shortening flow for exponents α > 1 2 . We show that any such curve having in addition its two ends asymptotic to two parallel lines, converges under α-curve shortening flow to the unique translating soliton whose ends are asymptotic to the same parallel lines. This is a new result even in the standard case α = 1, and we prove for all exponents up to the critical case α > 1 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Finally, we show that any ancient non-compact convex solution to the κ α flow, for all α ∈ (1/2, 1], must be a translating solution, therefore it is unique modulo rigid motions and parabolic rescalings by [14]. We remark that this in fact is a corollary of the more involved result [7,Theorem 1.1].…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…Finally, we show that any ancient non-compact convex solution to the κ α flow, for all α ∈ (1/2, 1], must be a translating solution, therefore it is unique modulo rigid motions and parabolic rescalings by [14]. We remark that this in fact is a corollary of the more involved result [7,Theorem 1.1].…”
Section: Introductionmentioning
confidence: 61%
“…Γ t − γ(e 2 , t) converges, as t → +∞ to a translator T 0 . In the case the solution is between two parallel lines, T 0 = T by [7,Theorem 1.1]. In case the solution is entire, then so is T 0 (which can be easily verified, for example by using translating solutions as barriers) and thus again T = T 0 .…”
Section: Classification Of Convex Ancient Solutionsmentioning
confidence: 94%
See 2 more Smart Citations
“…Recently, the authors [12] showed the convergence to a translating soliton for n = 1 and α > 1 2 . In this paper, we establish its higher dimensional result for n ≥ 2 as follows.…”
Section: Introductionmentioning
confidence: 99%